Hybrid perovskite light emitting diodes under intense electrical excitation. Issue 1 (December 2018) - Kim, Hoyeon; Zhao, Lianfeng; Price, Jared; Grede, Alex; Roh, Kwangdong; Brigeman, Alyssa; Lopez, Mike; Rand, Barry; Giebink, Noel
Abstract Hybrid perovskite semiconductors represent a promising platform for color-tunable light emitting diodes (LEDs) and lasers; however, the behavior of these materials under the intense electrical excitation required for electrically-pumped lasing remains unexplored. Here, we investigate methylammonium lead iodide-based perovskite LEDs under short pulsed drive at current densities up to 620 A cm−2 . At low current density (J  <  10 A cm−2 ), we find that the external quantum efficiency (EQE) depends strongly on the time-averaged history of the pulse train and show that this curiosity is associated with slow ion movement that changes the internal field distribution and trap density in the device. The impact of ions is less pronounced in the high current density regime (J  >  10 A cm−2 ), where EQE roll-off is dominated by a combination of Joule heating and charge imbalance yet shows no evidence of Auger loss, suggesting that operation at kA cm−2 current densities relevant for a laser diode should be within reach. Hybrid perovskite semiconductors are promising for wavelength-tunable laser diodes but their behavior under intense electrical excitation remains unexplored. Kim et al. investigate perovskite light emitting diodes at current densities nearing 1 kA cm−2 and suggest that a laser diode is within reach.